STUDI KARAKTERISTIK MARSHALL CAMPURAN ASPAL CONCRETE BEARING COARSE (AC BC) YANG MENGGUNAKAN BUTON GRANULAR ASPHALT (BGA) - Gaus, Abdul; W., Tjaronge M.; Ali, Nur; Djamaluddin, Rudy (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Buton Ganular buton asphalt is refined grains that has been produced mechanically so has quality and guaranteed quality compared with previous generationsasbuton. BGA uniformity of grain size and water content of not more than 2% make it superior to the previously produced asbuton.This paper discusses the use of BGA as an asphalt substitute petroleum in the bearing coarse mix asphalt concrete (AC BC). Topics studied in the asphalt mixture is marshall stability, flow and voids in mix (VIM). The use of BGA on asphalt mixture gives a positive influence so that used on roads with heavy traffic and intersections.